PARTICIPATION OF CIVIL SOCIETY IN THE RIGHT OF ACCESS TO PUBLIC INFORMATION - Morales Tostado , María del Carmen (UNIVERSIDAD DE SONORA, 2020)
In the present investigation, the legal framework of transparency and the right of access to public information is reviewed, based on the background of the human right to information from an international perspective, as well as, the evolution that the legal structure of transparency and the right to public information. Also, the citizenship construction process is reviewed, where the right of access to information becomes very important and the number of requests made to the National Institute for transparency, access to information and protection of personal data (INAI) is investigated from 2003 to 2019